Thanytt receives Malakoff Corporation Excellence Award - Siti Nurfarmy, Ibrahim (2022)
KUANTAN, 17 March 2022 - Thanytt s/o Pran Sek, 26, a graduand of Bachelor of Engineering Technology (Electrical) with Honours, received the Malakoff Corporation Bhd. Excellence Award that was established in 2019 in the 15th UMP Convocation Ceremony held at Dewan Jubli Perak Sultan Haji Ahmad Shah here recently.